KEMAMPUAN INTERAKSI SOSIAL PADA ANAK AUTIS - Endang Yuswatiningsih (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2021)
Social interaction is a real difficulty for autistic children to make social relations with their environment. The existence of disturbances in social interaction in children with autism can affect aspects of learning and behavior. The purpose of this study was to determine the social interaction ability of autistic children. The design of this research is descriptive. The population in this study was autistic children who were in the Seribu Warna Autistic Special School, Kepanjen Jombang, with as many as 50 respondents, with a total sample of 33 respondents using a purposive sampling technique. The variable in this study is the ability of social interaction. Data collection using the Autism Treatment Evaluation Checklist (ATEC). Data processing by editing, coding, scoring and tabulating. The results showed that the social interaction ability of autistic children had good criteria as many as 2 children (6.1%), almost all respondents had sufficient criteria as many as 27 children (81.8%), and a small proportion of respondents had fewer criteria as many as 4 children (12,1%). The conclusion in this study is that the social interaction ability of autistic children is sufficient in asking for help from friends, commenting on friends while playing, responding to invitations to play from friends, answering friends' questions, and following directions from friends. It is expected that the companion will provide time and opportunity for their students to conduct social interactions so that they can form better social relationships